Understanding approaches in urban planning for alleviating disaster impacts - Almeida, Jairo Filho Sousa de (2022)
Disasters have become one of the main problems in different parts of the world, affecting thousands of people directly or indirectly, making them homeless, missing, injured and dead, causing destruction wherever they are happening, and causing social and economic destruction that leads to billions in losses annually, making the creation and implementation of disaster mitigation and resilience policies a fundamental agenda in the context of urban planning. Like other sciences, urban planning accumulates precision and resources based on scientific academic research advances. This research aims to understand how current academic research on urban planning addresses disasters, catastrophes and calamities. The systematic literature review methodology was used to answer this research question, guided by the PRISMA protocol and using explicit inclusion and exclusion criteria. This research returns 301 papers on urban planning related to disasters, and the results were grouped according to the disaster category. The research gathered guidelines on how urban planning can reduce disaster risks and create adaptation and resilience mechanisms. The results led to the discussion of related issues, such as climate justice and the accelerated urbanization phenomenon, which appear to aggravate an increase in disasters.